Parasitismo de ovos de Erinnyis ello e Erinnyis alope em condicoes de campo - Farias, A.R.N.; Bellotti, Anthony C. (1983)
In order to determine the degree of parasitism of Erinnyis ello and E. alope eggs by Trichogramma and Telenomus under field conditions, 113 samples were collected, without determined dates, from Sept. 1978-March 1980, in Cruz das Almas, BA, Brazil, throughout the whole cassava cycle. Eggs were taken to the lab. and placed individually in vials for observation of parasitism. It was observed that from 3170 collected eggs 3031 (96 percent) were of E. ello and 139 (4 percent) of E. alope. From the E. ello eggs, 2120 (70 percent) larvae hatched and 713 (24 percent) were not fertile, being or not parasitized. From the E. alope, 110 (79 percent) larvae hatched. Of the total no. of E. ello eggs, 198 (6 percent) were parasitized by Trichogramma spp. and Telenomus sp., being 62 (31 percent) parasitized by Trichogramma and 136 (69 percent) by Telenomus. From the total no. of E. alope eggs collected, only 2 (1 percent) were parasitized by Telenomus. It was observed, also, that an av. 18.7 adults of Trichogramma emerged from each egg, with a min. of 5 and max. of 44, and for Telenomus, an av. 4.6 adults emerged from each egg, with min. of 1 and max. of 8. (AS)